2016
DOI: 10.1371/journal.pone.0161156
|View full text |Cite
|
Sign up to set email alerts
|

The Sense of Agency Is More Sensitive to Manipulations of Outcome than Movement-Related Feedback Irrespective of Sensory Modality

Abstract: The sense of agency describes the ability to experience oneself as the agent of one's own actions. Previous studies of the sense of agency manipulated the predicted sensory feedback related either to movement execution or to the movement’s outcome, for example by delaying the movement of a virtual hand or the onset of a tone that resulted from a button press. Such temporal sensorimotor discrepancies reduce the sense of agency. It remains unclear whether movement-related feedback is processed differently than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 47 publications
4
10
1
Order By: Relevance
“…In contrast, in studies showing suppression effects (including the current study), participants had to perform continuous movements with relatively large trajectories that were continuously displayed on a screen. It has been shown that participants are more sensitive to discrete action‐outcome asynchronies than to movement‐related feedback (David, Skoruppa, Gulberti, Schultz, & Engel, ). Moreover, it has been reported that sensory suppression specifically occurs during movement execution (Juravle, Deubel, Tan, & Spence, ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in studies showing suppression effects (including the current study), participants had to perform continuous movements with relatively large trajectories that were continuously displayed on a screen. It has been shown that participants are more sensitive to discrete action‐outcome asynchronies than to movement‐related feedback (David, Skoruppa, Gulberti, Schultz, & Engel, ). Moreover, it has been reported that sensory suppression specifically occurs during movement execution (Juravle, Deubel, Tan, & Spence, ).…”
Section: Discussionmentioning
confidence: 99%
“… Agency : the sense of having the subjective experience of action, i.e., “global motor control”. It is the feeling that the person is the agent of its own actions, and is highlighted if there is correspondence between the perceived and the actual consequence of an action (David et al, 2016 ). Body Ownership : one's self-attribution of a body.…”
Section: Introductionmentioning
confidence: 99%
“…The sense of agency is the feeling of control over one’s own action. This basic cognitive function allows to distinguish between self-generated and externally generated movements ( David et al, 2016 ). According to computational models of motor control such as the comparator model ( Frith et al, 2000 ; Blakemore et al, 2002 ; Chambon et al, 2014 ), a sense of agency arises from the matching between the predicted and the actual sensory outcome of intended actions.…”
Section: Introductionmentioning
confidence: 99%